The Influence of Multi-Channel Service Quality on Patient‎Satisfaction and Its Impact on Trust, Commitment, and The Behavioral ‎Intention of Outpatients At Siloam Hospital, Makassar - Conny, C.; Palilati, Alida; Sukotjo, Endro; Yusuf, Y (International Journal of Accounting and Economics Studies, 2025)
This study aims to develop the concept of multi-channel service quality by examining the role of two aspects: ‎e-servqual, encompassing efficiency, privacy, reliability, emotional benefit, and customer service; and servqual, ‎encompassing physical environment, personnel quality, and technical quality, in influencing patient ‎satisfaction. This study also examined the effect of satisfaction on patients’ behavioral intentions, mediated by ‎trust and commitment. The study recruited 384 outpatients from Siloam Hospital Makassar, with respondents ‎defined as patients with self-pay, company-funded, or insurance coverage who used the MySiloam app for ‎digital healthcare services. Data were collected using a Likert-based questionnaire. The collected data were then ‎analyzed descriptively and using PLS analysis. The results revealed that the aspects constituting multi-channel ‎service quality, e-servqual and servqual, encompassing efficiency, privacy, reliability, emotional benefit, ‎customer service, physical environment, personnel quality, and technical quality, had a positive and significant ‎influence on patient satisfaction. Furthermore, satisfaction was found to have a positive and significant ‎influence on trust, commitment, and behavioral intentions. Furthermore, trust and commitment partially ‎mediated the influence of satisfaction on behavioral intentions‎.
Keywords: Behavioral Intention; Commitment; Multi-Channel Service Quality; Satisfaction; Trust